Newly synthesized pyrimidine compound as CO 2 corrosion inhibitor for steel in highly aggressive simulated oilfield brine - Onyeachu I.; Quraishi M.A.; Obot I.B.; Haque J. (My University, 2025)
A newly synthesized pyrimidine–based compound, 5-(4-hydroxy-3-methoxyphenyl)-2,7-dithioxo-2,3,5,6,7,8-hexahydropyrimido[4,5-d]pyrimidin-4(1H)-one (PP), was evaluated as a promising inhibitor for the CO 2 corrosion of API X60 steel in NACE 1D196 brine solution. Under rotation speed of 1000 rpm, electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization (PDP) were complemented with scanning electron microscopy (SEM), X-ray diffraction (XRD) and Attenuated total reflectance infrared (ATR-IR) techniques to assess the corrosion inhibition performance. PP provided inhibition efficiency up to 90% at 20 ppm. It adsorbs on the Fe (110) phase on the steel using its heteroatoms and aromatic rings. Its adsorption greatly reduces the steel surface pitting corrosion. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.